Validity of microscopy for diagnosing urinary tract infection in general practice - a systematic review - Anja Kofod Beyer; Gloria Cristina Cordoba Currea; Anne Holm (Taylor & Francis Group, 2019)
Objective: To investigate the validity of microscopy as a diagnostic tool for urinary tract infection in general practice. Methods: (Design/setting) A systematic review was conducted by searching Medline for clinical studies made in general practice, outpatient clinics or similar settings in which the accuracy/validity of microscopy was evaluated with urine culture as the reference standard. Results: Our search resulted in 108 titles. 28 potentially eligible studies were retrieved for full-text reading. We included eight studies involving 4582 patients in this review. The quality of the studies was moderate to high. Specificity ranged from 27% to 100%, sensitivity from 47% to 97%. The variation between studies did not allow for meta-analysis. Conclusion: We did not find substantial evidence to determine the clinical validity of microscopy performed in general practice on urine samples from patients with symptoms of UTI.Key points Urinary tract infection is common in general practice. Methods for precise diagnosis are needed in order to avoid inappropriate treatment. Currently no evidence-based consensus exists regarding the use of urinary microscopy in general practice. We did not find substantial evidence to determine the overall clinical validity of microscopy performed in general practice on urine samples from patients with symptoms of UTI. Light microscopy with oil immersion had high sensitivity and specificity but is time-consuming. Phase-contrast microscopy is quick and had high specificity but lower sensitivity.